KAJIAN PUTUSAN PENGADILAN AGAMA SURAKARTA NOMOR 865/PDT.G/2024/PA.SKA DALAM PERSPEKTIF HUKUM PERDATA - Tanjung, Anwar Sadat; Marinka , Tifany Wulan; Paridian, Nurelia; Dewangga, Rizki; Ruslan, La Ode Muhammad; Wahyudi, Sri (PT Elaborium Elevasi Indonesia, 2025)
This study analyzes the Surakarta Religious Court Decision Number 865/Pdt.G/2024/PA.Ska, which concerns a divorce case arising from prolonged disputes, infidelity, and verbal abuse. The research employs a normative-juridical approach, focusing on the analysis of legal statutes, legal doctrines, and relevant jurisprudence. The methodology includes statutory, conceptual, and case-based approaches to evaluate the application of the principles of justice and legal certainty within Indonesia’s civil law system. The findings of this study indicate that the judge’s decision, conducted in absentia (verstek), aligns with the principles of justice and legal certainty. The judge ruled a talak one bain sughra based on strong evidence and witness testimony supporting the plaintiff. This decision not only protects the plaintiff’s rights but also sets an important precedent for addressing divorce cases in Indonesia. Furthermore, the findings show that the judiciary can provide adequate legal protection even in situations where the defendant is absent. Thus, the implications of this study emphasize the critical role of civil law in achieving substantive justice and maintaining social stability. The decision illustrates how law can serve as an instrument to protect vulnerable individuals, particularly women, while strengthening public trust in the legal system. This study also offers recommendations for enhancing guidelines to handle divorce cases involving prolonged disputes and verbal abuse.